2021
DOI: 10.7759/cureus.20072
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Risk Factors of COVID-19-Related Mortality

Abstract: IntroductionDuring the coronavirus disease 2019 (COVID-19) pandemic in India, several characteristics of hospitalized COVID-19 patients, based on demographics, mortality predictors, and presence of comorbidities, were found to be associated with poor outcomes. The objective of this study was to identify such epidemiological and clinical characteristics among the patients admitted at a tertiary-care center in India that may have predisposed them to COVID-19-related mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Ever since the beginning of the COVID-19 pandemic since 2019, attempts have been made to identify the determinants for the severe form of the disease. It was evident early on that the presence of comorbidities such as HTN, DM, CAD, CKD, malignancy, autoimmune disease, and immune-suppression due to transplantation contributed to a more severe form of the disease [12,13]. Such patients manifested a myriad of clinical features including ARDS and multi-organ failure.…”
Section: Discussionmentioning
confidence: 99%
“…Ever since the beginning of the COVID-19 pandemic since 2019, attempts have been made to identify the determinants for the severe form of the disease. It was evident early on that the presence of comorbidities such as HTN, DM, CAD, CKD, malignancy, autoimmune disease, and immune-suppression due to transplantation contributed to a more severe form of the disease [12,13]. Such patients manifested a myriad of clinical features including ARDS and multi-organ failure.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 is a recognized occupational hazard in Denmark ( 27 ), but the present findings indicate, that occupational COVID-19 may reach beyond the individual employee. Workplace-related infection of the spouse and other family members is in particular of concern for vulnerable people such as the elderly and people with a range of chronic diseases ( 28 , 29 ). This introduces a new perspective on management of occupational disease and adds to the importance of developing efficient preventive strategies, including for instance, consideration of strategies to mitigate domestic exposure and setting priorities for vaccination programmes ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…13,14,15 Multiple studies have confirmed that following SARS-CoV-2 infection, diabetics are more likely to be hospitalised as compared to non-diabetics, especially if there is poor glycaemic control. 16 Diabetes causes an inhibition in neutrophil chemotaxis, phagocytosis, and intracellular destruction of microbes, thus offering efficient virus entry and decreased viral clearance. 17…”
Section: Discussionmentioning
confidence: 99%